Dose Dependences of Phosphorescence and Сonduction Сurrent Relaxation in Single Crystals of Zinc Selenide - Degoda, V.Ya.; Podust, G.P.; Savchuk, V.R.; Kozhushko, B.V.; Bondar, M.V.; Tverdokhlibova, O.V. (Physics and Chemistry of Solid State, 2024)
At the excitation temperature, at least three types of traps (shallow, phosphorescent and deep) are involved in the processes of phosphorescence and relaxation of the conduction current. This necessitates the use of a crystal phosphorus multicenter model for which a theoretical dependence for between the intensity of phosphorescence and relaxation of the conduction current has been obtained. These dependences take into account the re-trapping of free charge carriers on shallower traps. The traps filling level depend not only on the total radiation dose but also on the intensity of excitation. For the doses of X-ray irradiation varying within four orders of magnitude, all experimental dependences of the intensity of phosphorescence and relaxation of the conduction current for ZnSe crystals are well described by the obtained theoretical dependences. The dose dependences of phosphorescence and conduction current relaxation which were obtained concurrently from different samples confirm that the trap release time for each type of the trap is determined not only by the probability of the thermal release of charge carriers from the traps, but also by the ratio of the concentration of an individual trap to the total concentration of the deeper traps.